eDNA metabarcoding in mangrove ecosystems for fish conservation and stock assessment of Sardinops sagax melanostictus in the Philippines - TRICKSIE P. BALATERO; ZILJIH MOLINA; RODELYN DALAYAP; RANDE DECHAVEZ; JANECE JEAN MANUBAG; NANETTE HOPE SUMAYA; JUSUA DELA PEÑA; SHARON ROSE TABUGO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Balatero TP, Molina Z, Dalayap RM, Dechavez R, Manubag JJ, Sumaya NH, Peña JD, Tabugo SRM. 2025. eDNA metabarcoding in mangrove ecosystems for fish conservation and stock assessment of Sardinops sagax melanostictus in the Philippines. Biodiversitas 26: 347-357. Mangrove forests are essential ecosystems that provide many benefits, including nursery grounds for various marine species; however, identifying juveniles is often challenging, as visual fish surveys primarily rely on the characteristics of adult specimens for accurate classification. These vital ecosystems are threatened by overfishing, habitat destruction, pollution, and climate change. Therefore, this study employs environmental DNA (eDNA) metabarcoding as a non-invasive tool to identify fish species in the mangrove ecosystems of Mindanao, Philippines. eDNA metabarcoding facilitates species detection by analyzing genetic material found in environmental samples, offering a cost-effective and sensitive method for identifying fish species. Seawater samples were collected from selected mangrove areas, and the extracted eDNA was analyzed using high-throughput next-generation sequencing (NGS). The sampling sites were South Cotabato, Surigao del Norte, Misamis Oriental, and Tawi-Tawi, which recorded 29 species across 20 families. Notable species included Zenarchopterus dunckeri (Zenarchopteridae), a rare fish in the aquarium hobby; Hippocampus comes (Syngnathidae), the tiger-tail seahorse, which is classified as Vulnerable by the IUCN; Sardinops melanostictus (Clupeidae), known for its high commercial value; Siganus corallinus (Siganidae), valued for both food and the aquarium trade; and Gymnothorax flavimarginatus (Muraenidae), an invasive species, that plays a vital role in the food chain as a natural predator of lionfish. Tawi-Tawi Island emerged as the most diverse site, recording species from 11 families. The results highlight the critical role of mangroves as nurseries in supporting diverse fish populations and underscore the effectiveness of eDNA metabarcoding as complementary to traditional species inventory techniques.